Ecology, Diversity, Antibiotic Resistance Of Lactic Acid Bacteria (LAB) Isolated From Plant Sources And Their Role In Natural Fermentation Of Tempoyak - Chuah, Li Oon (2016)
In recent years, bioprospecting of lactic acid bacteria (LAB) from plant sources contributes to the diversity of LAB and the discovery of novel application of LAB in food industries. As LAB play an important role in food fermentation, there are concern of dissemination of antibiotic resistance determinants harboured by the indigenous microbiota present in fresh fruits and fermented food through the food chain. The objectives of this study were to investigate the diversity and antibiotic resistance of LAB presence in fresh tropical fruits and flowers, as well as tempoyak produced by natural fermentation; to characterise the bacteriocin-like substances (BLIS) produced by these LAB isolates, and other technological properties.